For problems like these, multiply before factoring.
#=> (3x^2 - 3x+ 2x - 2)/(2x^2 + 4x + x + 2) xx (2x^2 + 2x + x + 1)/(3x^2 + 3x + 2x + 2)#
#=> (3x(x - 1) + 2(x - 1))/(2x(x + 2) + 1(x + 2)) xx (2x(x + 1) + 1(x + 1))/(3x(x + 1) + 2(x + 1))#
#=>((3x + 2)(x - 1))/((2x + 1)(x + 2)) xx ((2x + 1)(x + 1))/((3x + 2)(x + 1))#
Cancelling using the property #a/a = 1#, we get:
#=>(x - 1)/(x + 2)#
We should also note the restrictions on the original expression. These are found by setting both denominators to #0# and solving for #x#.
#2x^2 + 5x + 2 = 0" AND "3x^2 + 5x + 2 = 0#
#(2x + 1)(x + 2) = 0" AND "(3x + 2)(x + 1) = 0"#
#x = -1/2 and -2" AND "x = -2/3 and -1#
Hence, our restrictions are #x != -2, -1, -2/3, -1/2#.
Hopefully this helps!